Identifikasi Kualitas Fisik dan Kimia Air Sumur Gali di Wilayah Produksi Terasi di Dusun Jor Desa Jor Kecamatan Jerowaru Kabupaten Lombok Timur - Yuliansari, Dini; Fatmalia, Enida; Wahyudin, Wahyudin (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This research aims to determine the physical and chemical quality of dug well water in the area where shrimp paste (terasi) is produced at Jor Hamlet, Jor Village, Jerowaru Subdistrict, East Lombok Regency. The research method used was experimental, focusing on parameters such as temperature, pH, TDS, and hardness based on the Indonesian National Standard (SNI) guidelines. Three sampling points of community dug well water were selected with sampling conducted twice, considering the sampling points based on the distance between the dug wells and the shrimp paste production area being less than 10 meters, and due to the absence of proper wastewater disposal systems at the shrimp paste production site. From the results of the examination of the physical and chemical water quality around the shrimp paste production area in Jor Hamlet, Jor Village, Jerowaru Subdistrict, East Lombok Regency, it was found that several parameters met the requirements according to the Indonesian Ministry of Health Regulation Number 32 of 2017 concerning the Standard of Environmental Health Quality and Health Requirements for Hygiene, Swimming Pools, Solus Per Aqua, and Public Bathing. Parameters such as temperature, pH, and TDS met the standards. However, the examination revealed that the hardness of the dug well water exceeded the standard in one out of the three sampling points. Specifically, samples A and B met the standard for hardness, whereas sample C did not meet the standard because it exceeded the established quality standard of 500 mg/l.